Detoxification enzymes of Bemisia tabaci B and Q: biochemical characteristics and gene expression profiles. Issue 10 (8th April 2014) - Guo, Litao; Xie, Wen; Wang, Shaoli; Wu, Qingjun; Li, Rumei; Yang, Nina; Yang, Xin; Pan, Huipeng; Zhang, Youjun
Abstract BACKGROUND The sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), is one of the most invasive and destructive pests of field crops worldwide. The sibling species B and Q are the two most damaging members of the B. tabaci species complex. That Q is more resistant than B to many insecticides has been well documented. Over the last decade, Q has gradually displaced B and has become the dominant form of B. tabaci in field agricultural systems in most parts of China. To help understand the differences in insecticide resistance, the activities and gene expression profiles of detoxification enzymes in B. tabaci B and Q were investigated. RESULTS The activity of P450 towards 7‐ethoxycoumarin was significantly higher (1.46‐fold higher) in Q than in B. The expression of 43 of 65 P450 genes was higher (>1‐fold) in Q than in B, and expression for eight P450 genes was more than 50‐fold greater in Q than in B. The increased expression of selected P450 genes in Q relative to B was confirmed with two other B strains and two other Q strains. On the other hand, carboxylesterase (CarE) activity was significantly lower (0.71‐fold lower) in Q than in B; the Km value of CarE was significantly lower in B than in Q, but the opposite was true for the Vmax value of CarE. Glutathione S‐transferase activity and values of Km and Vmax did not differ between B and Q. CONCLUSION Enhanced metabolic detoxification of insecticides by P450s may be an important reason why B. tabaci Q is more resistant than B. tabaci B to insecticides. © 2014 Society of Chemical Industry